EFEKTIVITAS PENERAPAN PERATURAN DAERAH KABUPATEN KLUNGKUNG NOMOR 7 TAHUN 2014 TENTANG PENGELOLAAN SAMPAH - Ni Ketut Sri Ratmini; I Made Adi Widnyana; Budhi Sugandhika (Jurusan Hukum Fakultas Dharma Duta Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2023)
Regional Regulation of Klungkung Regency Number 7 of 2014 concerning Waste Management as the first step in combating problems starting from the management, manufacture (TPS) of Waste Disposal Sites, the formation of business entities (Waste Banks), as well as applying sanctions. In reality this arises from its roots, namely humans, people are less aware of the dangers of waste from flooding to disease, legal sanctions have been applied accordingly. Based on the background, the problems discussed in this study can be studied as follows: 1) The Effectiveness of the Implementation of the Klungkung Regency Regional Regulation on Waste Management? 2) Supporting and inhibiting factors for the enforcement of sanctions in the application of the Klungkung Regency Regional Regulation on Waste Management? This study refers to several relevant literatures, concepts and theories as a reference source, to be used as a scalpel against the formulation of the existing problem. The theory used is the Effectiveness of Law according to Lawrence M. Friedman, according to Soerjono Soekanto and the theory of the workings of law in society according to Robert B. Seidman. The method used in this research is empirical research, the nature of descriptive research, the form of qualitative data, primary and secondary data sources, data collection using observation methods, interviews, library research, determining research informants using purposive sampling techniques, research instruments using interview guidelines equipped with handphone, digital camera, recording, and with qualitative descriptive data analysis. The results of the research are as follows: 1. The local regulation of Klungkung Regency regarding Waste Management regarding the violation of littering has not been effective. 2. Supporting Factors such as Klungkung Regency Government Policies, the availability of 3R TPS and TPST in some areas, Satpol PP and DLH Klungkung Regency as supervisors and waste controllers in Klungkung Regency, supporting facilities and infrastructure for handling waste and inhibiting factors, regarding violations of littering there are factors that become obstacles, namely legal factors, law enforcement, facilities and infrastructure, society and culture. Efforts are made in divided into preventive efforts and reprentive efforts. From the results of the description above, it can be concluded that violations of littering still occur due to low public awareness and lack of socialization and supporting facilities. Keywords: Regional Regulation, Waste Management